Distribution of Ultraviolet Ornaments in Colias Butterflies (Lepidoptera: Pieridae). Issue 5 (31st July 2018) - Stella, David; Faltýnek Fric, Zdeněk; Rindoš, Michal; Kleisner, Karel; Pecháček, Pavel
Abstract: Ultraviolet patterns in butterflies have been recognized and studied for many years. They are frequently involved in both intraspecific and interspecific interactions. Only a handful of studies, however, have investigated possible links between ultraviolet (UV) reflectance and ecological properties in some genera of the Lepidoptera as a whole. This study examines the impact of habitat and distribution on UV reflectance patterns on the wings of 106 species and subspecies of Colias butterflies. Based on standardized digital photographs, we performed a multivariate analysis of relations between UV reflectance, preferred habitat (alpine, arctic, dry grasslands, humid, forest, and ubiquitous), and distribution area (Afrotropical, Nearctic, Neotropical, European, Caucaso–Anatolian, boreal Eurasian, Central Asian mountains, northern China and Japan, and northern Oriental region). UV patterns occur more frequently in the male (60 taxa) than in female (25 taxa) Coliads. This difference in presence of UV patterns is used for differentiating between the males and females of a given species or subspecies. Further possible explanations of this phenomenon are also discussed. This study also shows that particular configurations of UV patterns are significantly associated with particular distribution areas. This relation is relatively strong but overall trends remain unclear. Based on the results of this study, it can be concluded that there exists a significant difference in the configuration of UV reflectance between the sexes, and that the configuration of UV reflectance significantly interacts with the geographical distribution of Colias species and subspecies.